2014
DOI: 10.1016/j.canlet.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of miR-146a expression in a mouse model of pancreatic cancer affecting EGFR signaling

Abstract: Aberrant expression of microRNAs (miRNAs) plays important roles in the development and progression of pancreatic cancer (PC). Expression analysis of miR-146a in human PC tissues showed decreased expression in about 80% of samples compared to corresponding noncancerous tissue. Moreover, expression of miR-146a in eight PC cell lines, and in pancreatic tissues obtained from transgenic mouse models of K-Ras (K), Pdx1-Cre (C), K-Ras;Pdx1-Cre (KC) and K-Ras;Pdx1-Cre;INK4a/Arf (KCI), showed down-regulation of miR-146… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…Overexpression of miR‐146a was confirmed to suppress the migration and invasion of gastric cancer cells . Deregulation expression of miR‐146a affected EGFR signaling in pancreatic cancer model . In this study, it was found that miR‐146a was significantly low expression in prostate cancer tissues, suggesting possible biological significance in tumorigensis of prostate cancer.…”
Section: Discussionmentioning
confidence: 56%
“…Overexpression of miR‐146a was confirmed to suppress the migration and invasion of gastric cancer cells . Deregulation expression of miR‐146a affected EGFR signaling in pancreatic cancer model . In this study, it was found that miR‐146a was significantly low expression in prostate cancer tissues, suggesting possible biological significance in tumorigensis of prostate cancer.…”
Section: Discussionmentioning
confidence: 56%
“…Receptor activation leads to pro-growth and proliferation signaling Peta et al (2017), Kumaraswamy et al (2015), Ali et al (2014), Huang, He, Rong, Dang, and Chen (2014), Chen et al (2013), Xu et al (2012), Kogo et al (2011), Li et al (2010a, 2010b, Hurst et al (2009) NOTCH1/2 Endometrial, Esophageal, Glioblastoma…”
Section: Glioblastomamentioning
confidence: 99%
“…In gastric cancer, growing evidence has revealed the anti-tumor function of miR-146a-5p; it functions as a protective factor to repress neoplasm metastasis and tissue infiltration and to improve overall survival [47,48]. Recent studies have revealed that miR-146a-5p expression is lower in pancreatic cancer tissues than in non-tumor tissues based on analyses of miR-146a-5p levels in human tissue samples, cell lines, and mouse models by real-time PCR [49,50]. Our previous studies have confirmed that miR-146a-5p could clearly inhibit the deterioration of hepatocellular carcinoma [51,52].…”
Section: Discussionmentioning
confidence: 99%